2023
DOI: 10.3390/ph16020243
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin Improves Neuropathic Pain by Inhibiting the Expression of Chemokines and Inflammatory Factors in the Spinal Cord and Interfering with Glial Cell Polarization

Abstract: Neuropathic pain (NP) is a common pain disease that seriously affects the quality of life and physical and mental health of patients. Daphnetin is extracted from the Daphne giraldii Nitsche and has the structure of 7,8-dihydroxy coumarin. As a natural product, daphnetin displays a wide range of pharmacological activities, such as analgesia and anti-inflammatory activities, but whether it is able to improve NP through anti-inflammatory effects is unknown. Therefore, this paper intends to investigate the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It was shown that intrathecal CX3CL1 administration evokes strong mechanical and thermal hypersensitivity [45]. It was also shown that the mRNA level of this chemokine is elevated in the spinal cords of animals with neuropathy evoked by TNF-α injection [74]. Additionally, its upregulation is observed in the oxaliplatin model of neuropathic pain [46].…”
Section: Cx3c Chemokine In Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that intrathecal CX3CL1 administration evokes strong mechanical and thermal hypersensitivity [45]. It was also shown that the mRNA level of this chemokine is elevated in the spinal cords of animals with neuropathy evoked by TNF-α injection [74]. Additionally, its upregulation is observed in the oxaliplatin model of neuropathic pain [46].…”
Section: Cx3c Chemokine In Neuropathic Painmentioning
confidence: 99%
“…CXCR5 is a selective target of CXCL13; however, under physiological conditions in the CNS, it is expressed at a very low level [40]. Nevertheless, CXCL13 mRNA and/or protein levels increase in the spinal cord and/or DRGs in SNL- [40,68,72], CCI- [75], SpNI- [73], DB- [71], and TNFα-induced [74] neuropathic pain models. The intrathecal injection of CXCL13 induces pain hypersensitivity and astrocyte activation via CXCR5 [40].…”
Section: Chemokines In Neuropathic Painmentioning
confidence: 99%
“…In the neuropathic pain rats, daphnetin was demonstrated to suppress the expression of pro-inflammatory factors IL-1β, IL-6, and TNF-α, exerting neuroprotective effects. Meanwhile, daphnetin suppressed the activation of microglia, astrocytes, and neurons, thus reducing the nociceptive sensitization in neuropathic pain rats ( Zhang et al, 2023 ). In addition, in an experimental autoimmune encephalomyelitis (EAE) mice model, daphnetin (2 and 8 mg/kg) treatment significantly decreased lymphocyte infiltration and demyelination, which was attributed to reduction in pro-inflammatory factors, including TNF-α and IL-17 and an increase in anti-inflammatory factors, such as IL-4 and IL-10 ( Soltanmohammadi et al, 2022 ).…”
Section: Effects Of Daphnetin On Inflammatory Factorsmentioning
confidence: 99%
“…We used intrathecal injection for the administration of DAP to further clarify the effects of DAP in ameliorating NP at the spinal cord level and the mechanism of action. Our previous study found that DAP could inhibit the activation of spinal microglia in the TNF-α-induced NP rat model, which has profound implications for this study [ 14 ]. Therefore, during this study, we aimed to determine whether DAP can treat CCI-induced NP through spinal cord administration and explore the effects of DAP on the P2X 4 /P38 pathway of microglia under central sensitization conditions.…”
Section: Introductionmentioning
confidence: 99%